Photocurrents in P3MeT Schottky barrier diodes - Jones, G. W. (2015)
The photocurrent action spectrum of a Schottky diode formed from electrodeposited poly(3-methylthiophene) is shown to follow closely the UV-visible absorption spectrum. At low forward bias, the peak photocurrent asymptotes to the expected square-root dependence on total potential, V-t, across the depletion region. At high reverse bias the superlinear dependence of the photocurrent on V-t suggests that internal photoemission from the rectifying aluminium electrode may be the dominant process.